The causes and consequences of employee commitment to their organisations - Orpen, Christopher (2000)
The study tests a model of the antecedents and outcomes of organisational commitment among a sample of 101 Australian managers responsible for the overall quality of their organisation's goods and services. As hypothesised, personal characteristics, job attributes and work experiences influenced commitment. Commitment was also found to affect turnover intentions and attendance. However, commitment was unrelated to job performance, as rated by superiors. Implications of the findings are discussed. - Reproduced.
Keywords: Organizations; Employees; Managers